24th International Colloquium Tribology Industrial and Automotive Lubrication ; Conference documents 2024 - Dörr, Nicole; Gachot, Carsten; Marian, Max; Völkel, Katharina (expert Verlag, 2024)
The conference provides an international exchange forum for the industry and the academia. Leading university researchers present their latest findings, and representatives of the industry inspire scientists to develop new solutions
Keywords: Tribologie; Schmierstoff; Konferenzschrift -- 2024 -- Esslingen